Avaliação dos fragmentos florestais do município de Jaboticabal-SP - Greggio, Thiago Claudino; Tarle Pissarra, Teresa Cristina [UNESP]; Rodrigues, Flavia Mazzer [UNESP] (Univ Federal Vicosa, 2009)
This study was conducted inJaboticabal-SP, to evaluate the evolution and number of forest fragments in the period of 29 years, using remote sensing and photointerpretation techniques. The IBGE Maps (1971) and 2000 aerial photos were used to map the area. The reduction of the natural forest areas occurred during the time evaluated. In 1971, the municipality presented 3.63% of the total area in forest fragments, but only 1.55% of this area in 2000. This was due to the advance of agricultural practices, mainly sugarcane, in the area. The percentage of forest fragments lower than 10ha, in 1971, was 46.72% of the total area, but in 2000, this number increased to 78.51%, reaching a marked fragmentation process (31.79%) in the analyzed period. The forest fragments with higher extension in 1971 were extremely fragmented in 2000. Approximately 60% of these areas, at both times, presented long forms, indicating a high relation between perimeter and area.
Evaluation of forest fragment in Jaboticabal-SP
Keywords: Forest fragment; mapping and remote sensing